Targeting the DNA Damage Response for Cancer Therapy by Inhibiting the Kinase Wee1 - Bukhari, Amirali B.; Chan, Gordon K.; Gamper, Armin M. (Frontiers in Oncology, 2022)
Cancer cells typically heavily rely on the G2/M checkpoint to survive endogenous and exogenous DNA damage, such as genotoxic stress due to genome instability or radiation and chemotherapy. The key regulator of the G2/M checkpoint, the cyclin- dependent kinase 1 (CDK1), is tightly controlled, including by its phosphorylation state. This posttranslational modification, which is determined by the opposing activities of the phosphatase cdc25 and the kinase Wee1, allows for a more rapid response to cellular stress than via the synthesis or degradation of modulatory interacting proteins, such as p21 or cyclin B. Reducing Wee1 activity results in ectopic activation of CDK1 activity and drives premature entry into mitosis with unrepaired or under-replicated DNA and causing mitotic catastrophe. Here, we review efforts to use small molecule inhibitors of Wee1 for therapeutic purposes, including strategies to combine Wee1 inhibition with genotoxic agents, such as radiation therapy or drugs inducing replication stress, or inhibitors of pathways that show synthetic lethality with Wee1. Furthermore, it become increasingly clear that Wee1 inhibition can also modulate therapeutic immune responses. We will discuss the mechanisms underlying combination treatments identifying both cell intrinsic and systemic anti-tumour activities.